Preparation method of super duplex stainless steel seamless coil pipe
By controlling the chemical composition and preparation process of ultra-long duplex stainless steel seamless coils, the problem of prone to defects in the preparation process of stainless steel coils is solved, and high-precision and regular shape products are achieved, and production efficiency and finished product quality are improved. .
Patent Information
- Application Number
- CN202411626039.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing stainless steel coils are prone to defects such as cracks, deformation, scratches and other defects during the preparation process, which leads to difficulty in forming, affecting appearance quality and usage performance, and at the same time, they are low in production efficiency and irregular dimensional accuracy and shape.
By controlling the chemical composition and content of ultra-long duplex stainless steel seamless coils, we jointly control the processing processes and parameters of the preparation process, including ultrasonic detection, peeling, multi-channel rolling, disc pulling and annealing treatment, ensuring that the material is in the process. Avoid deformation or cracking.
The high precision and regular shape of super duplex stainless steel seamless coils are achieved, and defects such as cracks and deformation are avoided, the yield and quality are improved, and the continuous production of super duplex stainless steel seamless pipes is achieved.
Smart Images

Figure CN119456719A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coil preparation, and in particular to a method for preparing a super duplex stainless steel seamless coil. Background Art
[0002] Duplex stainless steel (DSS for short) refers to stainless steel in which ferrite and austenite each account for about 50%, and the content of the lesser phase generally needs to reach at least 30%. In the case of low C content, the Cr content is 18% to 28%, and the Ni content is 3% to 10%. Some steels also contain alloying elements such as Mo, Cu, Nb, Ti, and N. This type of steel has the characteristics of both austenitic and ferritic stainless steels. Compared with ferrite, it has higher plasticity and toughness, no room temperature brittleness, and significantly improved intergranular corrosion resistance and welding performance. At the same time, it also maintains the 475℃ brittleness of ferritic stainless steel and high thermal conductivity, and has the characteristics of superplasticity. Compared with austenitic stainless steel, it has high strength and significantly improved resistance to intergranular corrosion and chloride stress corrosion. Duplex stainless steel has excellent pitting corrosion resistance and is also a nickel-saving stainless steel.
[0003] In addition, stainless steel coil is a disc-shaped or mosquito-repellent ... In addition, for duplex stainless steel coils, the dimensional accuracy and shape are also important issues that need to be paid attention to during the preparation process. If the dimensional accuracy is not high or the shape is irregular, it will affect the installation and use of the coil. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a super duplex stainless steel seamless coil. The method provided by the present invention can prepare a super duplex stainless steel seamless coil with high dimensional accuracy, regular shape, no defects such as cracks and deformation, and can realize continuous production of super duplex stainless steel seamless pipes.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing an ultra-long duplex stainless steel seamless coil, wherein the ultra-long duplex stainless steel seamless coil comprises the following chemical components in percentage by mass:
[0007] C: 0.008-0.016%, Mn: 0.65-0.66%, P: 0.018-0.023%, S: 0.0004-0.0010%, Si: 0.6-0.8%, Ni: 4.5-6%, Cr: 26-27%, Mo: 3-4.7%, N: 0.26-0.29%, Ti: 0.02-0.04%, Cu: 0.05-0.10%, balance Fe;
[0008] The method for preparing the ultra-long duplex stainless steel seamless coil comprises the following steps:
[0009] The round bar containing the above-mentioned ultra-long duplex stainless steel material is subjected to first testing, peeling, punching and extrusion in sequence to obtain a hollow tube blank;
[0010] The hollow tube blank is subjected to a second inspection, a first pickling and a multi-pass rolling in sequence to obtain a rolled tube;
[0011] The rolled tube is sequentially subjected to a first annealing treatment, straightening, a second pickling and multiple coiling to obtain a coiled tube;
[0012] The coiled tube is subjected to a second annealing treatment, a third test and a post-treatment in sequence to obtain an ultra-long duplex stainless steel seamless coil tube.
[0013] Preferably, the ultra-long duplex stainless steel seamless coil comprises the following chemical components in percentage by mass:
[0014] C: 0.010~0.014%, Mn: 0.65~0.66%, P: 0.020~0.022%, S: 0.0005~0.0008%, Si: 0.7~0.78%, Ni: 4.7~5.8%, Cr: 26.2~26.8%, Mo: 3.5~4.4%, N: 0.265~0.28%, Ti: 0.023~0.038%, Cu: 0.055~0.08%, balance Fe.
[0015] Preferably, the first detection is ultrasonic detection.
[0016] Preferably, the multi-pass rolling is sixteen-pass rolling; the pre-rolling temperature of the multi-pass rolling is 520-650°C, and the final rolling temperature is 420-470°C.
[0017] Preferably, in the multi-pass rolling process, the reduction amounts of the first to sixth passes are independently 3-6%, and the reduction amounts of the seventh to sixteenth passes are independently 9-12%.
[0018] Preferably, the first annealing treatment is firstly to keep the temperature at 850-950° C. for 5-9 min, and then to keep the temperature at 950-1100° C. for 3-5 min.
[0019] Preferably, the multi-pass coil drawing comprises 5 to 15 passes of drawing, intermediate annealing and 3 to 8 passes of drawing in sequence.
[0020] Preferably, the pickling agent used for the second pickling is a mixed solution containing nitric acid, hydrofluoric acid, sulfuric acid and stannous chloride.
[0021] Preferably, the second annealing treatment is a bright heat treatment at 1080-1150° C. for 2-5 min in a hydrogen atmosphere.
[0022] Preferably, the post-processing includes loading onto a plate, performance testing, water pressure testing, air drying, coding and warehousing of finished products.
[0023] The present invention provides a method for preparing an ultra-long duplex stainless steel seamless coil. By controlling the chemical composition and content of the ultra-long duplex stainless steel seamless coil, the processing technology and parameters of the preparation process are coordinated to control the strength and strength of the prepared coil, and deformation or cracking of the material during processing or use is avoided, thereby improving the yield and quality of the product. The prepared super duplex stainless steel seamless coil has high dimensional accuracy, regular shape, and is free of defects such as cracks and deformation, and continuous production of super duplex stainless steel seamless pipes is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The present invention is a manufacturing flow chart of the ultra-long duplex stainless steel seamless coil. DETAILED DESCRIPTION
[0025] The present invention provides a method for preparing an ultra-long duplex stainless steel seamless coil, wherein the ultra-long duplex stainless steel seamless coil comprises the following chemical components in percentage by mass:
[0026] C: 0.008~0.016%, Mn: 0.65~0.66%, P: 0.018~0.023%, S: 0.0004~0.0010%, Si: 0.6~0.8%, Ni: 4.5~6%, Cr: 26~27%, Mo: 3~4.7%, N: 0.26~0.29%, Ti: 0.02~0.04%, Cu: 0.05~0.10%, balance Fe.
[0027] In the present invention, the ultra-long duplex stainless steel seamless coil preferably includes the following chemical components in mass percentage: C: 0.010-0.014%, Mn: 0.65-0.66%, P: 0.020-0.022%, S: 0.0005-0.0008%, Si: 0.7-0.78%, Ni: 4.7-5.8%, Cr: 26.2-26.8%, Mo: 3.5-4.4%, N: 0.265-0.28%, Ti: 0.023-0.038%, Cu: 0.055-0.08%, and the balance Fe. The present invention improves the corrosion resistance of the coil by adding a certain amount of chromium, molybdenum and nickel, improves the mechanical properties of the coil by adding a certain amount of carbon, silicon and manganese, improves the welding performance and processing performance of the coil by adding a certain amount of sulfur, titanium and phosphorus, and makes it easier to perform deformation operations such as stretching and bending during the preparation of the coil by synergistically adding a certain amount of titanium and copper, thereby producing the coil with high dimensional accuracy, regular shape, and no defects such as cracks and deformation, and controlling the chemical composition and content of the ultra-long duplex stainless steel seamless coil within the above range to obtain an ultra-long duplex stainless steel seamless coil with high comprehensive performance. In the present invention, the ultra-long duplex stainless steel seamless coil preferably contains unavoidable impurities.
[0028] In the present invention, the method for preparing the ultra-long duplex stainless steel seamless coil comprises the following steps:
[0029] The round bar containing the above-mentioned ultra-long duplex stainless steel material is subjected to first testing, peeling, punching and extrusion in sequence to obtain a hollow tube blank;
[0030] The hollow tube blank is subjected to a second inspection, a first pickling and a multi-pass rolling in sequence to obtain a rolled tube;
[0031] The rolled tube is sequentially subjected to a first annealing treatment, straightening, a second pickling and multiple coiling to obtain a coiled tube;
[0032] The coiled tube is subjected to a second annealing treatment, a third test and a post-treatment in sequence to obtain an ultra-long duplex stainless steel seamless coil tube.
[0033] In the present invention, unless otherwise specified, the raw materials used are conventional commercial products in the art.
[0034] The present invention sequentially performs first detection, peeling, punching and extrusion on a round bar containing the above-mentioned ultra-long duplex stainless steel material to obtain a hollow tube blank.
[0035] In the present invention, the first detection is preferably ultrasonic detection. The present invention completes a large number of pipeline inspections in a short time without causing any physical damage to the material through ultrasonic detection, thereby improving production efficiency and reducing detection costs; at the same time, ultrasonic detection can accurately identify and quantify defects inside the pipeline, such as cracks, pores, inclusions, etc., providing a reliable basis for quality control; through precise measurement and analysis, potential quality problems can be discovered and repaired in a timely manner to ensure the reliability and safety of the prepared coil. Moreover, ultrasonic detection can penetrate the wall of the stainless steel seamless coil and detect its internal defects, so that potential quality problems can be discovered and solved in a timely manner to ensure the reliability and durability of the stainless steel seamless coil.
[0036] The present invention removes impurities such as scale and oil stains on the surface of the pipe by peeling, reduces stress concentration and defects such as cracks inside the material, thereby improving the strength and toughness of the seamless pipe; peeling can also reduce the contact area between the seamless pipe and the external environment and reduce the corrosion rate. At the same time, peeling can also make the surface of the pipe more bright and smooth, which is conducive to coating adhesion and anti-corrosion treatment. The present invention has no characteristic restrictions on the method of punching and extrusion, and the technical solutions well known in the art can be used.
[0037] After obtaining the hollow tube blank, the present invention sequentially performs a second inspection, a first pickling and a multi-pass rolling on the hollow tube blank to obtain a rolled tube.
[0038] In the present invention, the second detection is preferably ultrasonic detection.
[0039] In the present invention, the pickling agent used in the first pickling is a mixed solution containing nitric acid, hydrofluoric acid and sulfuric acid; the pickling agent used in the first pickling is preferably prepared by a volume ratio of 1:1:0.5:80 of 20% nitric acid, 5% hydrofluoric acid, 10% sulfuric acid and water. The present invention removes oxides, rust and other impurities on the metal surface through the first pickling, providing a clean metal surface for subsequent processing and treatment.
[0040] In the present invention, the multi-pass rolling is preferably sixteen-pass rolling; the pre-rolling temperature of the multi-pass rolling is preferably 520-650°C, and the final rolling temperature is preferably 420-470°C. The present invention can promote grain refinement in the stainless steel material by controlling the pre-rolling temperature, and grain refinement helps to improve the strength and toughness of the material, thereby improving the comprehensive performance of the stainless steel seamless coil, and can also put the stainless steel material in a better plastic state, which is conducive to avoiding the generation of cracks and fractures during the rolling process, avoiding the pre-rolling temperature being too low, which may cause the material to be difficult to deform, or even cause equipment damage, and avoiding the temperature being too high, which may cause the material to overheat and oxidize severely, affecting the product quality.
[0041] In the present invention, in the multi-pass rolling process, the reduction amounts of the first to sixth passes are independently preferably 3-6%, and the reduction amounts of the seventh to sixteenth passes are independently preferably 9-12%. The present invention helps to obtain a smooth, defect-free surface by controlling the reduction amounts of the first to sixth passes and the seventh to sixteenth passes within the above range, thereby improving the durability of the prepared coil, while optimizing the microstructure of the material, improving the strength and toughness of the material, and facilitating the acquisition of the coil without defects such as cracks and deformation.
[0042] After the rolled tube is obtained, the invention sequentially performs a first annealing treatment, straightening, a second pickling and multiple coiling to obtain a coiled tube.
[0043] In the present invention, the first annealing treatment is preferably firstly carried out at 850-950° C. for 5-9 minutes, and then at 950-1100° C. for 3-5 minutes.
[0044] The present invention has no particular limitation on the straightening method and any technical solution known in the art may be used.
[0045] In the present invention, the pickling agent used in the second pickling is a mixed solution containing nitric acid, hydrofluoric acid, sulfuric acid and stannous chloride; the pickling agent used in the second pickling is preferably prepared by the preparation of 20% nitric acid, 5% hydrofluoric acid, 10% sulfuric acid, stannous chloride and water in the amount ratio of 1mL: 1mL: 0.5mL: (0.2-0.4)g: 80mL. The present invention removes oxides and rust on the metal surface at the same time through the second pickling, and forms a dense passivation film on the surface of the coil to improve corrosion resistance.
[0046] In the present invention, the multi-pass coil drawing preferably includes 5 to 15 passes of drawing, intermediate annealing and 3 to 8 passes of drawing in sequence. The present invention has no special limitation on the drawing method, and the coil of target size can be obtained by adopting the technical solutions well known in the art.
[0047] In the present invention, the temperature of the intermediate annealing treatment is preferably 980-1100° C. for 1-2 minutes in a hydrogen atmosphere. The present invention effectively eliminates the deformation strengthening effect through the intermediate annealing treatment, which helps to avoid cracks or fractures in the material during the subsequent drawing process, refine the grains, improve the strength and toughness of the material, effectively eliminate internal stress, and avoid deformation or cracking of the material during subsequent processing or use, thereby improving the yield and quality of the product, and producing the coil with high dimensional accuracy, regular shape, and no defects such as cracks and deformation.
[0048] After obtaining the coiled tube, the present invention sequentially performs a second annealing treatment, a third test and a post-treatment on the coiled tube to obtain an ultra-long duplex stainless steel seamless coil tube.
[0049] In the present invention, the second annealing treatment is preferably a bright heat treatment at 1080-1150°C in a hydrogen atmosphere for 2-5 minutes. The present invention effectively eliminates internal stress through the second annealing treatment, while improving the processing performance and corrosion resistance of the material, thereby obtaining an ultra-long duplex stainless steel seamless coil with good comprehensive performance.
[0050] In the present invention, the post-processing preferably includes loading onto a plate, performance testing, water pressure testing, air drying, coding and finished product storage.
[0051] The present invention has no special restrictions on the methods of mounting, performance testing, water pressure testing, air drying, and coding, and adopts technical solutions well known in the art.
[0052] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] Example 1
[0054] The ultra-long duplex stainless steel seamless coil is composed of the following chemical components in mass percentage: C: 0.012%, Mn: 0.65%, P: 0.021%, S: 0.0005%, Si: 0.72%, Ni: 4.9%, Cr: 26.6%, Mo: 3.5-4.4%, N: 0.265%, Ti: 0.026%, Cu: 0.065%, and the balance Fe.
[0055] The preparation method of the above-mentioned ultra-long duplex stainless steel seamless coil comprises the following steps:
[0056] The Ø245 round bar containing the above-mentioned super-long duplex stainless steel material is subjected to ultrasonic testing and then peeled to obtain a Ø243 round bar, punched to obtain a Ø45 tube blank, and then extruded to obtain a Ø89*12 hollow tube blank;
[0057] The hollow tube blank is tested to be qualified by ultrasonic testing, and is first pickled with a pickling agent prepared by mixing 20% nitric acid, 5% hydrofluoric acid, 10% sulfuric acid and water in a volume ratio of 1:1:0.5:80, and then rolled in multiple passes to obtain a Φ19*1.5 rolled tube;
[0058] The multi-pass rolling is sixteen-pass rolling; the pre-rolling temperature of the multi-pass rolling is preferably 530°C, and the final rolling temperature is preferably 450°C; during the multi-pass rolling process, the reduction amounts of the first to sixth passes are 5%, and the reduction amounts of the seventh to sixteenth passes are 11%;
[0059] The rolled tube is first kept at 880° C. for 6 minutes, then kept at 980° C. for 3 minutes, straightened, and then secondly pickled with a pickling agent prepared by a dosage ratio of 1 mL: 1 mL: 0.5 mL: (0.2-0.4) g: 80 mL of 20% nitric acid, 5% hydrofluoric acid, 10% sulfuric acid, stannous chloride and water, and subjected to multiple coiling to obtain a 9.53*1.65*200 coiled tube;
[0060] The multi-pass coil drawing is firstly performed 5 to 15 passes of drawing, then heat treated at 980° C. for 1 minute in a hydrogen atmosphere, and then performed 3 to 8 passes of drawing;
[0061] The coiled tube is subjected to bright heat treatment at 1080° C. for 3 minutes in a hydrogen atmosphere, and subjected to ultrasonic testing and post-treatment to obtain an ultra-long duplex stainless steel seamless coil tube;
[0062] The post-processing includes, in sequence, mounting on a plate, performance testing, water pressure testing, air drying, coding and warehousing of finished products.
[0063] Example 2
[0064] The ultra-long duplex stainless steel seamless coil is composed of the following chemical components in mass percentage: C: 0.012%, Mn: 0.65%, P: 0.021%, S: 0.0005%, Si: 0.72%, Ni: 4.9%, Cr: 26.6%, Mo: 3.5-4.4%, N: 0.265%, Ti: 0.030%, Cu: 0.065%, and the balance Fe.
[0065] The ultra-long duplex stainless steel seamless coil of Example 2 was prepared according to the method of Example 1.
[0066] Example 3
[0067] The ultra-long duplex stainless steel seamless coil is composed of the following chemical components in mass percentage: C: 0.012%, Mn: 0.65%, P: 0.021%, S: 0.0005%, Si: 0.72%, Ni: 4.9%, Cr: 26.6%, Mo: 3.5-4.4%, N: 0.265%, Ti: 0.034%, Cu: 0.065%, and the balance Fe.
[0068] The ultra-long duplex stainless steel seamless coil of Example 2 was prepared according to the method of Example 1.
[0069] Example 4
[0070] Ultra-long duplex stainless steel seamless coils were prepared according to the method of Example 1, except that during the multi-pass coiling process, the intermediate annealing treatment was: heat treatment at 990° C. for 1 min in a hydrogen atmosphere.
[0071] Example 5
[0072] Ultra-long duplex stainless steel seamless coils were prepared according to the method of Example 1, except that the intermediate annealing treatment during the multi-pass coiling process was heat treatment at 1000° C. for 1 min in a hydrogen atmosphere.
[0073] Example 6
[0074] Ultra-long duplex stainless steel seamless coils were prepared according to the method of Example 1, except that during the multi-pass coiling process, the intermediate annealing treatment was: heat treatment at 1100° C. for 1 min in a hydrogen atmosphere.
[0075] The ultra-long duplex stainless steel seamless coils prepared in Examples 1 to 6 were subjected to the following performance tests, and the results are shown in Table 1.
[0076] (1) Tensile test
[0077] API arc tensile test pieces were cut from the ultra-long duplex stainless steel seamless coils prepared in Examples 1 to 6 in accordance with the API-5CT standard so that the tensile direction was the tube axis direction. The cut test pieces were subjected to a tensile test in accordance with the API standard, and the yield strength YS (MPa) and the tensile strength TS (MPa) were measured as tensile properties.
[0078] (2) Charpy impact test
[0079] V-notch test pieces (5 mm thick) were cut from the central part of the wall thickness of the ultra-long duplex stainless steel seamless coils prepared in Examples 1 to 6 in accordance with ISO-11960 so that the length of the tube is the length of the test piece. The Charpy impact test was performed on the cut test pieces at a test temperature of -10°C to measure the absorbed energy vE -10 (J) It should be noted that three test pieces were cut from each steel pipe, and the Charpy impact test was performed on these test pieces. The arithmetic mean of the obtained values is shown in Table 2.
[0080] (3) Corrosion test (carbon dioxide corrosion resistance test)
[0081] Corrosion test pieces of 3 mm in thickness, 30 mm in width, and 40 mm in length were prepared by machining the ultra-long duplex stainless steel seamless coils prepared in Examples 1 to 6. These test pieces were subjected to corrosion tests to evaluate carbon dioxide corrosion resistance.
[0082] In the corrosion test, the test piece is immersed in a test liquid maintained in an autoclave: a 20 mass% NaCl aqueous solution (liquid temperature: 200°C, CO2: 3.0MPa atmosphere), and the immersion period is set to 14 days (336 hours). The mass of the test piece after the test is measured, and the corrosion rate is calculated from the mass reduction before and after the corrosion test. In addition, for the test piece after the corrosion test, a magnifying glass with a magnification of 10 times is used to observe whether pitting occurs on the surface of the test piece. It should be noted that pitting refers to the situation where pitting with a diameter of more than 0.2mm exists when the pitting is assumed to be circular. In the present invention, the corrosion rate is less than 0.125mm / year, and the situation where no pitting occurs is evaluated as qualified.
[0083] (4) Sulfide stress cracking resistance test (SSC resistance test)
[0084] The ultra-long duplex stainless steel seamless coils prepared in Examples 1 to 6 were respectively machined into round rod-shaped test pieces (diameter: 6.4 mmφ) according to NACE TM0177 Method A, and these test pieces were subjected to SSC resistance test. In the SSC resistance test, the test pieces were immersed in an aqueous solution adjusted to pH 3.5 by adding acetic acid + sodium acetate to the test liquid: 20wt% NaCl aqueous solution (liquid temperature: 25°C, H2S: 0.03MPa, CO2: 0.07MPa atmosphere), and the immersion period was set to 720 hours, and 90% of the additional yield stress was added as the additional stress. For the test pieces after the test, the presence or absence of cracks was visually observed. In addition, for the test pieces after the test, the presence or absence of pitting on the surface of the test pieces was observed using a magnifying glass with a magnification of 10 times. In the present invention, the test pieces after the test were evaluated as qualified if there was no cracking and no pitting.
[0085] (5) Sulfide stress corrosion cracking resistance test (SCC resistance test)
[0086] From the seamless steel pipe subjected to the above-mentioned heat treatment, a 4-point bending test piece with a thickness of 3mm×width of 15mm×length of 115mm was cut by machining, and the test piece was subjected to an SCC resistance test. In the SCC resistance test, the test piece was immersed in a test liquid maintained in an autoclave: a 10wt% NaCl aqueous solution (liquid temperature: 80°C, H2S: 35kPa, CO2: 2MPa atmosphere), the immersion period was set to 720 hours, and 100% of the additional yield stress was applied as the additional stress. For the test piece after the test, the presence or absence of cracks on the surface of the test piece was visually observed. In addition, for the test piece after the test, a magnifying glass with a magnification of 10 times was used to observe the presence or absence of pitting on the surface of the test piece. In the present invention, the test piece after the test was evaluated as qualified if there was no cracking and no pitting.
[0087] Table 1 Performance statistics of ultra-long duplex stainless steel seamless coils prepared in Examples 1 to 6
[0088]
[0089]
[0090] It can be seen from Table 1 that the ultra-long duplex stainless steel seamless coils prepared in Examples 1 to 6 of the present invention have high tensile strength, good toughness, and excellent resistance to sulfide stress cracking and sulfide stress corrosion cracking.
[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an ultra-long duplex stainless steel seamless coil, characterized in that: The ultra-long duplex stainless steel seamless coil comprises the following chemical components in mass percentage: C: 0.008-0.016%, Mn: 0.65-0.66%, P: 0.018-0.023%, S: 0.0004-0.0010%, Si: 0.6-0.8%, Ni: 4.5-6%, Cr: 26-27%, Mo: 3-4.7%, N: 0.26-0.29%, Ti: 0.02-0.04%, Cu: 0.05-0.10%, balance Fe; The method for preparing the ultra-long duplex stainless steel seamless coil comprises the following steps: The round bar containing the above-mentioned ultra-long duplex stainless steel material is subjected to first testing, peeling, punching and extrusion in sequence to obtain a hollow tube blank; The hollow tube blank is subjected to a second inspection, a first pickling and a multi-pass rolling in sequence to obtain a rolled tube; The rolled tube is sequentially subjected to a first annealing treatment, straightening, a second pickling and multiple coiling to obtain a coiled tube; The coiled tube is subjected to a second annealing treatment, a third test and a post-treatment in sequence to obtain an ultra-long duplex stainless steel seamless coil tube.
2. The method for preparing the ultra-long duplex stainless steel seamless coil according to claim 1, characterized in that: The ultra-long duplex stainless steel seamless coil comprises the following chemical components in mass percentage: C: 0.010~0.014%, Mn: 0.65~0.66%, P: 0.020~0.022%, S: 0.0005~0.0008%, Si: 0.7~0.78%, Ni: 4.7~5.8%, Cr: 26.2~26.8%, Mo: 3.5~4.4%, N: 0.265~0.28%, Ti: 0.023~0.038%, Cu: 0.055~0.08%, balance Fe.
3. The method for preparing the ultra-long duplex stainless steel seamless coil according to claim 1, characterized in that: The first detection is ultrasonic detection.
4. The method for preparing the ultra-long duplex stainless steel seamless coil according to claim 1, characterized in that: The multi-pass rolling is sixteen-pass rolling; the pre-rolling temperature of the multi-pass rolling is 520-650°C, and the final rolling temperature is 420-470°C.
5. The method for preparing the ultra-long duplex stainless steel seamless coil according to claim 4, characterized in that: In the multi-pass rolling process, the reduction amounts of the first to sixth passes are independently 3-6%, and the reduction amounts of the seventh to sixteenth passes are independently 9-12%.
6. The method for preparing the ultra-long duplex stainless steel seamless coil according to claim 1, characterized in that: The first annealing treatment is firstly to keep the temperature at 850-950° C. for 5-9 minutes, and then to keep the temperature at 950-1100° C. for 3-5 minutes.
7. The method for preparing the ultra-long duplex stainless steel seamless coil according to claim 1, characterized in that: The multi-pass coil drawing includes 5 to 15 passes of drawing, intermediate annealing treatment and 3 to 8 passes of drawing in sequence.
8. The method for preparing an ultra-long duplex stainless steel seamless coil according to claim 1, characterized in that: The pickling agent used in the second pickling is a mixed solution containing nitric acid, hydrofluoric acid, sulfuric acid and stannous chloride.
9. The method for preparing an ultra-long duplex stainless steel seamless coil according to claim 1, characterized in that: The second annealing treatment is bright heat treatment at 1080-1150° C. for 2-5 minutes in a hydrogen atmosphere.
10. The method for preparing an ultra-long duplex stainless steel seamless coil according to claim 1, characterized in that: The post-processing includes loading on a plate, performance testing, water pressure testing, air drying, coding and warehousing of finished products.
Citation Information
Patent Citations
Long rectangular hollow conductor processing method
CN102820101A
Drawing production process of monel alloy pipe
CN103817168A
Duplex stainless steel wire and preparation method thereof
CN105624580A
Manufacturing method of superaustenitic 904L stainless steel seamless steel pipe coiled pipe
CN107377666A
High-strength corrosion-resistant anti-crack steel as well as preparation method and application thereof
CN115852268A